92.2k views
1 vote
Which statement best describes the effect on the graph of y = (x – 9)2 if the equation is changed to y = (x + 9)2? The graph moves up 18 units. The graph moves down 18 units. The graph moves left 18 units. The graph moves right 18 units.

2 Answers

3 votes

Answer:

The graph moves left 18 units.

Explanation:

User Nour Sammour
by
5.9k points
4 votes

Answer:

Third option: The graph moves left 18 units.

Explanation:

Some transformations for a function f(x) are shown below:

If
f(x)+k, the function is shifted up "k" units.

If
f(x)-k, the function is shifted down "k" units.

If
f(x+k), the function is shifted left "k" units.

If
f(x-k), the function is shifted right "k" units.

In this case, we can observe that graph of
y = (x - 9)^2 is changed to
y = (x + 9)^2

Since:


-9+18=9

We can conclude that the function
y = (x - 9)^2 is shifted left 18 units to get the function
y = (x + 9)^2.

User Ismnoiet
by
5.9k points